Role of oxidative stress and apoptosis in the placental pathology of Plasmodium berghei infected mice. - Lalita Sharma (Public Library of Science (PLoS), 2012)
Placental malaria is a common clinical complication during pregnancy and is associated with abortion, premature delivery, intrauterine growth retardation and low birth weight. The present study was designed to delineate the underlying mechanism of placental pathology during malarial infection with special reference to oxidative stress and apoptosis. Experimentally, pregnant BALB/c mice were infected with Plasmodium berghei infected red blood cells on gestation day 10. The presence of malarial infection in placenta was confirmed by histopathological studies. It was observation that infected placenta had plugged placental sinusoids with parasitized red blood cells and malarial pigments. Interestingly, we found significant increase in the level of malondialdehyde, the index of oxidative stress and decreased activity of catalase, the antioxidant in infected placenta. Furthermore, in infected placenta the oxidative stress mediated apoptosis was determined by DNA fragmentation assay, ethidium bromide/acridine orange staining and caspase activity. It was observed that oxidative stress begin after second day of malarial infection. Interestingly, it was observed that there was down regulation of anti-apoptotic protein Bcl-2 and up regulation of pro-apoptotic protein Bax in infected placenta, suggesting the involvement of mitochondrial pathway of apoptosis which was further confirmed by activation of caspase 9. However, no change in the expression of Fas gene and caspase 8 activity, indicated the absence of death receptor pathway. Thus, it can be concluded that the placental pathology during malarial infection is mediated by mitochondrial pathway of apoptosis occurring due to augmented lipid peroxidation which may in turn jeopardise the materno-fetal relationship.